Possibilities of electronic marketing and electronic communications for the present - A. V. Balabanova (Путеводитель предпринимателя)
In the article the analysis of the modern media space from the point of view of opportunities and characteristics of electronic communication and opportunities given by marketing on the worldwide wide area network Internet is provided. The characteristic of Internet advertizing is considered, its features and opportunities for customers and suppliers of marketing services are analyzed. In the article it is shown that use of technologies of the virtual reality allows to move to absolutely new qualitative level of development in different knowledge domains already now.